Evaluation of Repair Bond Strength for Aged Resin-Based CAD/CAM Blocks and Indirect Inlay Composite Materials - Gurses, Merve; Ulku, Sultan Gizem; Erol, Ahmet; Unlu, Nimet (UI Scholars Hub, 2024)
Objective: This study aims to evaluate the repair bond strength of aged resin-based CAD/CAM blocks and indirect composites after surface treatment and application of adhesives. Methods: In the study, Lava Ultimate, Ceresmart, Filtek Z550, Filtek Ultimate, and Estelite Quick restorative materials; SE Bond, and Optibond XTR adhesives were used. For surface treatments, 37% orthophosphoric acid and 9% hydrofluoric acid were applied. In the control groups, only adhesive was applied. After repair restorations, the shear bond strength test was applied. Results: In the Lava group of SE Bond, the bonding values of the samples treated with 9% hydrofluoric acid were significantly higher than those treated with 37% phosphoric acid. Comparing the composites, in the samples treated with 37% phosphoric acid, we found the binding values of the Lava to be significantly lower than those of the FZ550, FU, and Estelite. In the OptiBond group, the binding values of the GC Cerec in the control group were lower than those in the FZ550, FU, Estelite, and Lava. Conclusion: It was observed that the repair bond values of the indirect composites were comparable. The repair bond values of the resin-based CAD/CAM blocks are similar but lower than those of the other indirect composites.